Peningkatan Hasil Belajar Siswa Kelas IX SMP Negeri 2 Jeunieb melalui Pemanfaatan Media Audio Visual pada Materi Qurban dan Aqiqah - Nasriati Nasriati; Nurbayani Nurbayani (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
The low learning outcomes of class IX students of SMP Negeri 2 Jeunieb are due to the lack of direct student involvement in the learning process. To overcome this problem, conducted classroom action research (CAR) through the use of Audio Visual Media. The purpose of this study was to determine the increase in student activity and learning outcomes by using Audio Visual Media for class IX at SMP Negeri 2 Jeunieb. The research subjects consisted of 30 students. The source of the research data was obtained from qualitative data in the form of data from observations of teacher and student activities as well as quantitative data in the form of test data on student learning outcomes. The results of the first cycle of research on the ability to understand qurban and aqiqah material after using audio-visual media reached a class average of 54% in the less good category. The implementation of cycle II was able to improve the learning process of cycle I. This was shown in the class average test scores of 81.73%. This was also shown in students being more active in learning, they held discussions to find good learning outcomes, were able to work in groups and able to understand qurban and aqiqah material well. Teacher activities in cycle II also show that teachers are more prepared, able to motivate students and able to explain material well and carry out their main role as facilitators and student assistants in conducting discussions to find a learning outcome. Based on these research results, learning using Audio Visual Media can improve the learning outcomes of class IX students of SMP Negeri 2 Jeunieb.